Whole-Genome Sequencing: An Effective Strategy for Insertion Information Analysis of Foreign Genes in Transgenic Plants - Wang, Xu-jing; Jiao, Yue; Ma, Shuo; Yang, Jiang-tao; Wang, Zhi-xing (Frontiers in Plant Science, 2020)
Molecular characterization is a key step in the risk assessment of GMOs for regulatory approval. Herein, we describe a method for analyzing copy number, insertion loci, and flanking sequences through WGS and bioinformatics. Comprehensive molecular characterization of G2-6 transgenic rice was performed using this pipeline. The results showed that one copy of the foreign gene was inserted into rice chromosome 8. There was no vector backbone insertion but an unexpected insertion and DNA rearrangement at the 3’ end of the T-DNA. We also obtained the 5’ and 3’ flanking sequences of the T-DNA. Our results suggested that the use of a combination of WGS and bioinformatics is an effective strategy for the molecular characterization of GMOs